KAJIAN SOSIOLINGUISTIK: SIKAP BAHASA GENERASI MUDA TERHADAP BAHASA LAMPUNG DI BANDAR LAMPUNG - Sofiyana, Rosa; Bela, Selsa; Sari, Mei Fatmila; Al Farabi, Muhammad Ramdhan Fathin; Kartika, Atik (Jurnal Tiyuh Lampung: Pendidikan Bahasa dan Kebudayaan, 2025)
This sociolinguistic study explores the language attitudes of young generations towards the Lampung language in Bandar Lampung, addressing the critical issue of local language vitality in the era of globalization. Employing a qualitative literature review methodology, the research analyzed academic publications from 2014-2024 focusing on language attitudes, sociolinguistics, and regional language preservation. Through comprehensive data extraction and thematic analysis, the study identified three primary factors influencing young people's language attitudes: globalization and modernization, education and media, and social structural changes. The findings reveal a significant decline in Lampung language usage among youth, highlighting its diminishing attractiveness as a communication tool and local identity symbol. The research contributes theoretical insights into the dynamic relationship between language attitudes, cultural identity, and modernization challenges, emphasizing youth's crucial role as social change agents. Strategic recommendations include holistic preservation approaches, educational program development, cultural expression platforms, and leveraging digital technologies to revitalize the Lampung language.   Studi sosiolinguistik ini mengeksplorasi sikap bahasa generasi muda terhadap bahasa Lampung di Bandar Lampung, dengan menyoroti isu penting mengenai vitalitas bahasa lokal di era globalisasi. Dengan menggunakan metodologi tinjauan literatur kualitatif, penelitian ini menganalisis publikasi akademik dari tahun 2014-2024 yang berfokus pada sikap bahasa, sosiolinguistik, dan pelestarian bahasa daerah. Melalui ekstraksi data yang komprehensif dan analisis tematik, studi ini mengidentifikasi tiga faktor utama yang memengaruhi sikap bahasa anak muda: globalisasi dan modernisasi, pendidikan dan media, serta perubahan struktur sosial. Temuan penelitian menunjukkan penurunan yang signifikan dalam penggunaan bahasa Lampung di kalangan remaja, menyoroti berkurangnya daya tarik bahasa ini sebagai alat komunikasi dan simbol identitas lokal. Penelitian ini memberikan wawasan teoritis mengenai hubungan dinamis antara sikap bahasa, identitas budaya, dan tantangan modernisasi, dengan menekankan peran generasi muda.